2016
DOI: 10.15201/hungeobull.65.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Detection of atmospheric urban heat island through direct measurements in Cluj-Napoca city, Romania

Abstract: In the last decades, cities worldwide have experienced accelerated development, so that continuous urbanization and its impact is presently one of the most important topics in diff erent fi elds of research. The main aim of this study is to identify the intensity of the atmospheric urban heat island in Cluj-Napoca city, through direct observations campaigns by using fi xed points and transect measurements. The data has been collected over a period of 6 months (May-October 2015). The measurements have been perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…It can be observed that the most extensive areas with LST > 35°C, LST > 38°C and LST > 40°C are located in the northeastern part of the city, these results being in line with the direct observations made by Herbel et al (2016) who have shown that the hottest places are located in the eastern half of Cluj-Napoca municipality.…”
Section: (Source: Authors)supporting
confidence: 88%
See 1 more Smart Citation
“…It can be observed that the most extensive areas with LST > 35°C, LST > 38°C and LST > 40°C are located in the northeastern part of the city, these results being in line with the direct observations made by Herbel et al (2016) who have shown that the hottest places are located in the eastern half of Cluj-Napoca municipality.…”
Section: (Source: Authors)supporting
confidence: 88%
“…In Romania LST estimations in an urban area were made by Imbroane et al (2014), based on Landsat satellite images, for the city Cluj-Napoca, and by Herbel et al (2016), who have been detecting atmospheric urban heat islands. Likewise, in regards to detecting atmospheric urban heat islands based on Modis satellite images we can mention Apostol et al, (2012) for the municipality of Iasi and Cheval & Dumitrescu (2009, 2015 for Bucharest.…”
Section: Introductionmentioning
confidence: 99%
“…ere are several ways to study urban heat island. ey include: appropriately designed, purposeful climatological networks (Herbel et al 2016), remote sensing methods (Roth, Oke, Emery 1989;Tran et al 2006;Fabrizi, Bonafoni, Biondi 2010), traverse (or mobile) measurement (Quitt 1978) or modelling (Atkinson 2003).…”
Section: Urban Heat Island Modellingmentioning
confidence: 99%
“…Cheval and Dumitrescu (2014) and Cheval et al (2015) presented the first results from the enhanced network for UHI monitoring in Bucharest. Herbel et al (2016) assessed UHI in Cluj-Napoca city. Marques et al (2015) performed heat stress assessment of two contrasted outdoor urban environments in two European capitals -Bucharest and Lisbon in order to examine thermal physiological response to heat stress and to quantify the effect of urban green spaces.…”
Section: Countries With Average Otc Research Productionmentioning
confidence: 99%